Adaptasi Visual Motif Gambar Fauna pada Produk Scarf Hijab Modis Brand Alzena Kids Moslem - Suliastuti, Iftika; Destiarmand, Achmad Haldani (Serat Rupa: Journal of Design, 2023)
Fauna motifs hold social and cultural significance as symbolism in their application to cultural artifacts. Fauna decorative motifs applied to fashionable scarves and hijabs have religious limitations, as depicting fauna images is strictly prohibited and considered a form of associating partners with Allah SWT in the Islamic religion. One of the fauna motifs explored in this research is the representation of imaginary living creatures. The topic addressed in this study is the analysis of fauna motif designs using a visual adaptation strategy approach, with a focus on aesthetic elements in the printed fauna motifs of the Alzena Kids Moslem brand's fashionable hijabs. The fauna motif that serves as the brand's identity within the broader context of Muslim fashion is the Unicorn image. The Unicorn, also known as Qilin in Chinese history, is an adaptation of a horse-like creature with unique features, including a horn. This research aims to understand the reasons behind brands incorporating depictions of living creatures in the visual adaptation of fauna motif designs on printed scarf hijabs. The research methodology employed is qualitative descriptive research with a visual adaptation approach. The study examines the aesthetic elements through the theory of visual adaptation strategies as parameters for analyzing the research objects. The analysis of objects is conducted by collecting hijab products with fauna motif designs obtained from observations at the Indonesia Hijab Festival 2022 exhibition. This research is conducted to map out the designs and adaptation strategies of printed fashionable hijabs featuring fauna motifs from the Alzena Kids Moslem brand.